(Non)discriminatory treatment of the cohabitation partners regarding the right to survivor´s pension - Grubešić, Ivana; Radončić, Dženana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
This paper was inspired by a recent decision of the Constitutional Court of Bosnia and Herzegovina, which establishes the existance of unequal treatment of marital and cohabitation partners regarding the exercise of the right to survivor´s pension, as one of the key property rights deriving from the family union. Such a progressive interpretation comes as a follow-up to an earlier decision of the same Court finding discrimination of cohabitation partners in comparison to spouses with respect to inheritance rights. The authors of the paper agree with the conclusions of the Constitutional Court of BiH in both of these decisions, but partly for other reasons, which is why they consider it important to supplement the argumentation and reasoning used in said decisions. The paper therefore first outlines trends in the case law of the European Court of Human Rights, followed by an analysis of relevant legislation in BiH, in order to examine, within the discrimination test, whether the BiH legislature has adequately used the discretionary space to create and implement public social security policies, and whether, based on the entire legal regime set up for the cohabitation union, it created legitimate (justifiable) expectations for the extramarital partners (bona fide) that their de facto extra-marital cohabitation is equalized in property effects with the marital community.